Biography of a Writer as an Object of Literary Studies - Zaborskaitė, Vanda (Problemos, 1986)
A growing interest in biography of a writer can be traced in the literary studies of late. Scholars tend to write either thoroughly documented biographies applying psychoanalytic data without any stylization or studies where the biography of a writer, typical for his period, is presented in the context of literary culture of the period. The works by V. Kuzmickas, J. Žėkaitė, R. Mikšytė and others display increasing interest in Lithuanian biographical literary studies.